2023
DOI: 10.1177/00139165231163550
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Pedestrians’ Perceptions of Safety, Comfort, and Pleasantness Induced by Public Space Lighting: A Systematic Literature Review

Abstract: Public space lighting (PSL), if adequately designed, may significantly enhance pedestrians’ sense of safety and comfort. Yet, the accumulated knowledge about subjective evaluation of PSL is still insufficient. This paper presents a systematic literature review, carried out according to the PRISMA guidelines, of factors affecting pedestrians’ perceptions of safety, comfort, and pleasantness induced by PSL. The screening process, which focused on studies combining technical- and observer-based environmental asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…These results are significant in view of the importance of sport and recreational activities as part of a healthy lifestyle in today's society and the efforts of public authorities to provide a range of sports facilities to meet these needs [142]. Some authors have analysed which is the most suitable lighting for pedestrians [143][144][145], cycling [49,146] and sports [147]. Nonetheless, to the best of the authors' knowledge, scarce research has analysed lighting perceptions in the context of recreational activities [148], such as running, from the point of view of citizens themselves.…”
Section: Discussionmentioning
confidence: 99%
“…These results are significant in view of the importance of sport and recreational activities as part of a healthy lifestyle in today's society and the efforts of public authorities to provide a range of sports facilities to meet these needs [142]. Some authors have analysed which is the most suitable lighting for pedestrians [143][144][145], cycling [49,146] and sports [147]. Nonetheless, to the best of the authors' knowledge, scarce research has analysed lighting perceptions in the context of recreational activities [148], such as running, from the point of view of citizens themselves.…”
Section: Discussionmentioning
confidence: 99%
“…But despite the wide street, the sidewalk is confined to one side, while the other is used for parking spaces, lawns, and access to lots. As discussed before, the importance of this variable is a matter not just of vitality but also of public security (Trop et al, 2023).…”
Section: Source: Based On Foundations Of Urban Morphology and Vitalitymentioning
confidence: 95%
“…between D and the others can be noted, a relatively higher weighted average (12.5), due to lighting conditions and to the presence of nighttime activities (Trop, Tavory & Portnov, 2023;Zhu et al, 2023).…”
mentioning
confidence: 98%
“…"A new review of the first 50 articles showed that though some of these studies included an overview of gender in their sampling, only six had a gender perspective on perceived safety [16]. A review [26] found that five of the 1315 articles they reviewed focused on how lighting influenced women's perception of safety. The review concluded: "…important knowledge gap is related to the insufficient representation of cultural or ethnic groups."…”
Section: Literature Reviewmentioning
confidence: 99%